Perlindungan Konsumen Laundry Dalam Perjanjian Baku Pada Usaha Cha Cha Laundry - Ni Nyoman Diah Widiasih; Ni Luh Mahendrawati; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2021)
A Service wash or known as laundry has made many people easier in working because it could save their daily life. However, most of the consumers are aggrieved by the standard form contract between two parties where the therms and contracts are set by one of the parties. The formulation of the problems in this study are 1. What is the form of consumer protection for laundry against laundry standard agreements? 2. What are the legal consequences if there is default on the laundry standard agreement? The research method used is an empirical method. In the case, this contract is set by the owner whose ability is higher to negotiate more favorable terms. Therefore, there is a need for legal protection for laundry consumers according to the Consumer Protection. Both parties-the owner and consumer-are wired to make deals if it is associated with the article 1320 on Indonesian Civil Code. The protections law for the consumer of the laundry service regarding to the standard form contract is the owner is obligated to pay damages if he/she is in default or tort. Whereas, if there is a default on laundry service’s strandard from contract, it can be canceled by law, because the owner should pay damages as the consumer has rights and obligations as had been regulated in article 4 and 5 of act number 8, 1999 on Consumer Protection.